Zgraditi džamijo je ustavna pravica - Teršek, Andraž (Pravnik, 2015)
In 2004 the author of the present paper was also the author of the initiative for constitutional legal consideration of the request to call a referendum concerning the building of the Islamic religious facilities, the mosque in Ljubljana, submitted to the Constitutional Court of the Republic of Slovenia to decide on. In the introduction it first gives an outline of the social and political developments that accompanied the pre-referendum campaign. In part one he first expounds the process and constitutional legal reasons because of which in this case the Constitutional Court was able to carry out constitutional juridical assessment of the content of the referendum via the act on the call of the referendum. Further it analyses the content aspect of the referendum request - also and with the help of comparative legal approach - provides constitutional legislative reasons that support the judgement of content unconstitutionality of this concrete referendum. Theoretically the constitutional legislation problem of the goal, the objective, or the purpose pursued by a definite legislative measure - either passed by the usual legislator or in the case when voters take over the legislative function in a referendum - is discussed separately. Explained are the selection and the use of constitutional texts for decisions in this kind of cases. The author also analyses the problem of the relationship between the Islamic religious community and the majority population through the provisions of the Constitution on equality of religious communities, on the freedom of conscience, and the freedom of creed. In the concluding part he presents the key parts from the argumentation of the Constitutional Court why this referendum initiative was anti-constitutional. He concludes the text with a presentation of the latest Slovenian constitutional juridical precedence that outlines all the essential characteristics of constitutional legislative protection of religious freedom and equality in Slovenian constitutional order.
Keywords: človekove pravice; freedom of religion; human rights; ustavne pravice; ustavno pravo; verska svoboda